إعمال العقل في فهم القرآن الحكيم وعلاقته بالأسلوب المعرفي : طلبة الجامعة الإسلامية العالمية بماليزيا نموذجا - هنائية، بدرية علي وليد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study combines the sciences of Quran and the cognitive psychology in terms of cognitive methods. The purpose of this study was to know the cognitive methods of the students from the Department of Quran Studies and the Sunnah and its impact on their understanding of the Holy Quran. The research followed the inductive method. The methodology, controls, factors and application of the realization of reason in understanding the Quran and in psychology were viewed by the researcher in written and audio formats. This study had also followed an analytical approach as it traced and determined relationships between the different research variables using different field tools. For instance, the first one used a famous psychological test known as The Matching Familiar Figure Test which was given to the students of Quran and Sunnah Studies only. The second tool used surve، interviews with the same representative sample who were considered as references in their specialties to test their level of using the realization of reason when understanding the Holy Quran. The results of the study reveal that there is a positive relationship between the meditation-based cognitive method and the level of using the realization of reason when understanding the Holy Quran. For example, the students who embraced a cognitive method based on meditation were able to understand the Quranic verses more efficiently. They were able to understand the Quranic words in terms of knowing the relationship between the words and their meaning, knowing their meaning in different Quranic contexts, knowing the literal and metaphoric usage of the words and predicted deleted words from the Quranic context. They were also able to connect the verses with each other, link them to the core of Sura, deduce the explicit and implicit Quranic directives, as well as, clear the illusion of the existence of verses that contradict each other. They were also able to know when to follow the concept of disagreement. On the other hand, the study found that the most prominent obstacles facing students in understanding the Quran are metaphor, rhetoric and grammar. Moreover, the most important weaknesses among the sample are deducing the implicit directives from Quranic verses and deciding on when to apply the divergent meaning. The research recommends the need to reinforce the students' abilities and address their weaknesses.